DEVELOPMENT OF METHODOLOGY FOR MANAGING THE ACTIVITIES OF VERTICALLY INTEGRATED INDUSTRIAL ENTERPRISES - Mullabayev Baxtiyarjon Bulturbayevich; Muminova Maxbuba Abduvafoyevna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article, innovation processes are becoming a major factor in the development of innovative processes and the sustainability of economic growth and innovation. In this regard, the article draws attention to the strategic management of innovative processes and the scheme of organizing innovative strategy strategies for the enterprise. Innovative strategy has studied the work carried out in this field in the country by studying the impact of the company's competitive development on innovations in individual enterprises and on the entire economy.